Greenwashing and Consumer Green Perceived Value: The Mediation Mechanism of Green Consumer Confusion and Green Perceived Risk - LIANG, Yaru; CHENG, Cheng (Journal of Environmental Management and Tourism; Vol 16 No 2 (2025): JEMT, Volume XVI, Issue 2(78), Summer 2025DO - 10.14505/jemt.v16.2(78).07, 2025)
Amid rising consumer awareness and regulatory scrutiny of corporate sustainability claims, greenwashing has become a pressing concern in green marketing. This study investigates the impact of greenwashing on consumer perceptions by examining its influence on green perceived value, consumer confusion, and green perceived risk. Specifically, it explores the mediating roles of consumer confusion and green perceived risk in the relationship between greenwashing and green perceived value. Using structural equation modeling (SEM) and a dataset of 299 responses from green product consumers in China, the findings indicate that greenwashing significantly diminishes green perceived value. Notably, consumer confusion emerges as a critical mediator, amplifying the negative effect of greenwashing by leading to flawed purchasing decisions. However, contrary to expectations, green perceived risk does not mediate this relationship, suggesting the presence of cognitive biases or other unexamined factors influencing consumer decision-making. These findings contribute to the literature on green marketing by revealing the nuanced mechanisms through which greenwashing affects consumer evaluations. They also highlight the need for businesses to implement transparent and authentic green marketing strategies to preserve consumer trust and perceived value. Furthermore, this study provides novel insights into the complex interplay between green perceived risk and consumer judgment, paving the way for future research on sustainable marketing practices.